1998
DOI: 10.1038/sj.onc.1201827
|View full text |Cite
|
Sign up to set email alerts
|

Photoproducts in transcriptionally active DNA induce signal transduction to the delayed U.V.-responsive genes for collagenase and metallothionein

Abstract: Mammalian cells in culture react to ultraviolet irradiation with the massive transcriptional activation of several genes and with the stabilization of the p53 protein. While U.V.-induced transcription of several immediate-response genes depends on U.V.-induced activation of signal transduction generated by non-nuclear mechanisms, stabilization of p53 and the transcription of several delayed-response genes are triggered by U.V.-induced DNA damage. By comparing dose responses for the activation by U.V. of delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 38 publications
10
37
0
Order By: Relevance
“…In agreement with other observations in similar cell systems and comparable UV doses (Li et al, 1996;Ljungman and Zhang, 1996;Blattner et al, 1998;McKay et al, 1998), normal ®broblasts showed fast stabilization of p53 protein, rapid activation of bax and p21 (whose kinetics of induction closely follow p53) and late activation of Mdm2 (that rises markedly 24 h after irradiation). In XP-A ®broblasts the fast increase in p53 and activation of bax and p21 were not followed by Mdm2 activation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In agreement with other observations in similar cell systems and comparable UV doses (Li et al, 1996;Ljungman and Zhang, 1996;Blattner et al, 1998;McKay et al, 1998), normal ®broblasts showed fast stabilization of p53 protein, rapid activation of bax and p21 (whose kinetics of induction closely follow p53) and late activation of Mdm2 (that rises markedly 24 h after irradiation). In XP-A ®broblasts the fast increase in p53 and activation of bax and p21 were not followed by Mdm2 activation.…”
Section: Discussionsupporting
confidence: 78%
“…Accumulating experimental evidence suggests that the induction of the p53 response by UV is not triggered by DNA strand breaks but rather, is linked to inhibition of transcription due to persistent DNA damage (Ljungman et al, 1999). Among the various photoproducts, the major trigger for UV-induced apoptosis may be the presence of CPDs (Dumaz et al, 1997(Dumaz et al, , 1998Blattner et al, 1998). This is further supported by our results in CS cells which normally remove (6-4)P from the transcribed strand of active genes whereas they are speci®cally defective in CPD removal (Barrett et al, 1991;Parris and Kraemer, 1993;Evans and Bohr, 1994).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A possible explanation for this discrepancy might be that not all dimers are equal, but that repair of a fraction of dimers might have disproportionate effects on biological responses. This hypothesis is supported by the recent observation that only photoproducts in actively transcribed DNA, which are preferentially repaired (30) and constitute only a small fraction of the total DNA, are important in signal transduction (31). Perhaps DNA regions involved in the transcriptional regulation of the human ICAM-1 gene may be repaired more rapidly than others may.…”
Section: Discussionsupporting
confidence: 64%
“…4,5 In addition, less distorting but highly mutagenic lesions, such as O 6 -methyl guanine, can be converted from non-blocking lesions into blocking lesions by the binding of mismatch repair proteins to the lesions. 6 Using human cell lines or mouse models with specific defects in nucleotide excision repair, it has been shown that the induction of p53 [7][8][9][10][11][12] and apoptosis 8 following UV-irradiation depends on persistent lesions localized in the transcribed strand of active genes. Furthermore, a number of agents that interfere with RNA polymerase II-mediated transcription have been shown to induce p53 and apoptosis suggesting that blockage of transcription may act as a trigger for stress response activation.…”
Section: The Transcription Stress Response (Tsr)mentioning
confidence: 99%